The Influence of GGBFS as an Additive Replacement on the Kinetics of Cement Hydration and the Mechanical Properties of Cement Mortars - Dražan Jozić; Branimir Ljubičić; Andrija Petrović; Anđela Čović; Sandra Juradin (Buildings, 2023)
Granulated blast furnace slag (GBFS) is a byproduct of the iron production process. The objective of this study is to determine the effects of ground granulated blast furnace slag (GGBFS), used as a replacement admixture (0–40 wt.%) for ordinary Portland cement (OPC), on the setting time, the heat of hydration, and the mechanical properties of cement mortar. The influence of GGBFS as a replacement additive on the setting time shows that it has an accelerating effect on cement hydration. Calorimetric measurements were performed on the cement paste system to determine the effects of GGBFS on the hydration of OPC. Calorimetric measurements carried out show that the replacement of GGBFS in an amount up to 40 wt.% reduces the total heat of hydration by up to 26.36% compared to the reference specimen. The kinetic analysis performed on the calorimetric data confirms the role of GGBFS as an accelerator by shortening the time during which the process of nucleation and growth (NG), as the most active part of hydration, is reduced up to 2.5 h. The value of the Avrami–Erofee constant indicates polydispersity and heterogeneous crystallization. Mechanical tests of cement mortars were performed after 3, 7, 14, 28, 70, and 90 days of hydration and showed that replacement addition of GGBFS slightly reduced the mechanical properties in the early phase of hydration, while in the later phase of hydration it contributed to an increase in the mechanical properties.